Luteolin supplementation ameliorates cobalt-induced oxidative stress and inflammation by suppressing NF-кB/Kim-1 signaling in the heart and kidney of rats (2020)
Cobalt-induced cardiomyopathy and renal toxicity have been reported in workers in processing plants, hard metal industries, diamond polishing and manufacture of ceramics. This study was designed to investigate the influence of Luteolin supplementation on cobalt-induced cardiac and renal toxicity in rats. Exposure of rats to cobalt chloride (CoCl2) alone caused significant (p < 0.05) increases in cardiac and renal H2O2, malondialdehyde (MDA) and nitric oxide (NO), along with increased serum myeloperoxidase (MPO) activity. In addition, there were significant (p < 0.05) reductions in cardiac and renal glutathione peroxidase (GPx), glutathione S-transferase (GST) and reduced glutathione (GSH). CoCl2 induced higher immuno-staining of nuclear factor kappa beta (NF-κB) in the heart and kidneys, and the kidney injury molecule (Kim-1) in the kidneys. Treatment with Luteolin or Gallic acid produced significant reversal of the oxidative stress parameters with reductions in NF-κB and Kim-1 expressions, leading to suppression of histopathological lesions observed in the tissues.